If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6m + -9)(5m + 5) = 0 Reorder the terms: (-9 + 6m)(5m + 5) = 0 Reorder the terms: (-9 + 6m)(5 + 5m) = 0 Multiply (-9 + 6m) * (5 + 5m) (-9(5 + 5m) + 6m * (5 + 5m)) = 0 ((5 * -9 + 5m * -9) + 6m * (5 + 5m)) = 0 ((-45 + -45m) + 6m * (5 + 5m)) = 0 (-45 + -45m + (5 * 6m + 5m * 6m)) = 0 (-45 + -45m + (30m + 30m2)) = 0 Combine like terms: -45m + 30m = -15m (-45 + -15m + 30m2) = 0 Solving -45 + -15m + 30m2 = 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), '15'. 15(-3 + -1m + 2m2) = 0 Factor a trinomial. 15((-1 + -1m)(3 + -2m)) = 0 Ignore the factor 15.Subproblem 1
Set the factor '(-1 + -1m)' equal to zero and attempt to solve: Simplifying -1 + -1m = 0 Solving -1 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1m = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1m = 0 + 1 -1m = 0 + 1 Combine like terms: 0 + 1 = 1 -1m = 1 Divide each side by '-1'. m = -1 Simplifying m = -1Subproblem 2
Set the factor '(3 + -2m)' equal to zero and attempt to solve: Simplifying 3 + -2m = 0 Solving 3 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2m = 0 + -3 -2m = 0 + -3 Combine like terms: 0 + -3 = -3 -2m = -3 Divide each side by '-2'. m = 1.5 Simplifying m = 1.5Solution
m = {-1, 1.5}
| 4(3x-3)-3=4(x-3)+45 | | .84=8+34ln(x) | | 16-r/y=21 | | 2x+16=5x+3 | | 6/16=9/t | | 22x+20=180 | | (-3/15)-(-10/15) | | 5t^3(t-4t)=0 | | 2x-36=18 | | 2u+5=-7 | | 6/10x1/100 | | T-4t=0 | | 8.6=-log(x) | | X^2+12x+23=-9 | | Z-46=59 | | 56÷7/656 | | 56÷7/6 | | y+5=108 | | 4.20=0.75 | | 4(3x+1)(x-4)=0 | | 2(1+4)=16 | | (x-6).7=49 | | a-9=34 | | 12x^2-25x-7= | | 4x+5-9=2x-5 | | 3x+5y+3x+2y= | | 31=6.2-y | | 20x*20x= | | 3m-9=-6 | | 21(1/3) | | 9-n-7= | | 20x+20x= |